The critical thinking skill of mathematics education students during pandemic: A Review - Ni Made Intan Kertiyani; Ketut Sarjana (Jurnal Pijar Mipa, 2022)
Learning in higher education is expected to be able to optimize students' critical thinking skills. However, learning mathematics during the pandemic encountered many obstacles affecting students' critical thinking skills. Furthermore, even before the pandemic occurs, mathematics education students still face difficulties optimizing their critical thinking skills. This study aims to analyze the level of critical thinking skills of mathematics education students during the pandemic and the learning models that can be applied to improve these abilities through online learning. The method used is a systematic literature review (SLR) on Google Scholar, ERIC, Science Direct, and DOAJ databases restricted for publish year in 2019-2022. The findings are the level of critical thinking ability of mathematics education students varies depending on the course used in the research. Secondly, several models or learning media can be applied in online classes during the pandemic to improve the critical thinking skills of mathematics education students. Some of them are a combination of Google meet with scaffolding-based online Geogebra, E-Academic based on collaborative learning, PDEODE strategy. The use of Geogebra Javascript, Realistic Mathematics Education approach, Problem Based Learning, using e-books instead conventional books and articles in newspapers as learning media.